Pengaruh Promo Gratis Ongkos Kirim Terhadap Minat Beli di Shopee : (Studi Kasus Pada Masyarakat Kelurahan Pasar Maga) - Cahyani Aulia Fitri; Sari Fitri; Mufti Fahrizal (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
This research aims to determine the effect of free shipping promotions on buying interest at Shopee (case study in the Pasar Maga sub-district community. Type of quantitative research, data collection techniques using observation and distributing questionnaires. The sample consisted of 60 respondents using the observation method and distributing questionnaires. Slovin Formula. Data analysis techniques use validity tests, reliability tests, normality tests, p-plot graphs, heteroscedasticity tests, scatterplot graphs, simple linear regression analysis tests and hypothesis tests using the SPSS version 25 program on buying interest at Shopee (Case Study in Pasar Maga Village Community), the tcount value for the Free Shipping Promo variable (X) is 5.604 with a ttable value of 1.671. So the tcount value is greater than ttable (5.604 > 1.671. This means that the free shipping promo has a positive effect on buying interest as proven by this research with The R Square value is 0.351 x 100% = 35.1%. while the remaining 64.9% is explained by other variables. Apart from that, the free shipping promo variable has a moderate relationship with shopee buying interest among the people of Pasar Maga Village, Mandailing Natal Regency, amounting to 0.593 which is in the correlation interval of 0.40 – 0.599 according to table 3.7.